THE VIDEO OF “SUMPING” (HUSBANDS’ SUPPORT ACCOMPANY) ON HUSBANDS’ MOTIVATION IN ACCOMPANYING THE CHILDBIRTH IN ISLAND AREA - Utami Dewi; Rahmadona, Rahmadona; Nurniati Tianastia Rullyni (International Journal of Social Science, 2022)
Reducing the incidence of childbirth complications requires the role of the family (especially the husband). Besides, the improvement of husbands’ participation in reproductive health is to provide husbands with information and to include husbands in every effort to improve reproductive health. One of the activities that husbands can do to improve the health of mothers and children is to accompany their wives during the delivery process. The design of this study was quasi-experimental with a post-test-only control group design. In addition, the treatment given to the respondents was a video "SUMPING" (Husbands’ Support Accompany) to find out the difference in motivation between the treated and non-treated groups. In addition, the sample in this study was part of the birth attendant at PMB Tanjungpinang City, which was divided into two groups: treatment and control groups. Also, the minimum sample is 30 for each group; therefore, the total sample is 60 people. Furthermore, the sampling technique used purposive sampling following the inclusion criteria. Thus, this study concludes that the "SUMPING" video has effectively increased the husband’s motivation to accompany the mother during childbirth because it attracts attention, increases respondents’ interest, and easy to understand. Hopefully, the "SUMPING" video can be a recommendation as a media for health education to husbands in the pregnant women class program and prepare for husbands to accompany the mother’s childbirth